Konseling Kelompok Untuk Peningkatan Motivasi Belajar Dengan Pendekatan SFBC (Teknik Miracle Question) - Wijayanti, Tega (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2020)
Motivation to learn is something to stimulate students in carrying out learning activities to get a goal, namely achievement in learning. In learning activities, there will be active interactions that lead to the physical and mental development of students. So the authors conducted research on "Group Counseling To Increase Learning Motivation With SFBC (Miracle Question Technique) Approach To Students Class XI IPA 2 SMA Hang Tuah 1 Surabaya". The aim was to see if the SFBC approach to magic questioning techniques had an effect on increasing learning motivation. Retrieval of research subjects was carried out using data methods in the form of measuring learning motivation, data from interviews with subject teachers about the conditions of students' activeness during learning activities, activeness in carrying out assignments, and the accuracy of task orders. Based on the descriptive analysis, the proportion of large motivation to learn in class XI IPA 2 is 5.56% has very high learning motivation, 30.56% has high learning motivation, 47.22% has moderate learning motivation, and 16.67% has low motivation to learn. The author tries to help increase motivation to learn with the magic question technique because the essence of every human being is able to build solutions to improve his life. The author seeks to help students to find solutions with barriers, strengths, and weaknesses themselves. Because the learning motivation factor is the dominant factor, it is sought for further research to analyze the factors that influence learning motivation, for example learning environments, learning resources and learning media.